Transdisciplinary Multispectral Modeling and Cooperation for the Preservation of Cultural Heritage - (:unkn) unknown (My University, 2026)
This book constitutes the refereed proceedings of the 4th International Conference on Transdisciplinary Multispectral Modelling and Cooperation for the Preservation of Cultural Heritage Addressing World Challenges, TMM-CH 2025, held in Athens, Greece during April 7-9, 2025. The 38 full papers included in this volume were carefully reviewed and selected from 477 submissions. They were categorized under the topical sections as follows: Developments in Digital Heritage; Utilization of IT and Digital Technologies for Sustainable Preservation, Revealing and Management of Cultural Heritage; and Digital Technologies for the Evaluation of the Resilience of Cultural Heritage Assets to Climate Change and Natural Hazards.
Keywords: Cultural Heritage; Digital Heritage; Virtual Heritage; Digital Documentation; Extended Reality; IoT; Artificial Intelligence; Heritage Management